2008
DOI: 10.1016/s1081-1206(10)60227-x
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptions for self-injectable epinephrine and follow-up referral in emergency department patients presenting with anaphylaxis

Abstract: Background-Anaphylaxis guidelines recommend that patients with a history of anaphylactic reaction should carry self-injectable epinephrine and should be referred to an allergist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 21 publications
7
57
0
3
Order By: Relevance
“…Data from several cohort studies illustrate the extent of under-treatment of anaphylaxis and the low rate of adrenaline use (12,15,(39)(40)(41), with most cases of anaphylaxis that require hospitalization not receiving an AAI on discharge. Adrenaline is much less commonly used than antihistamines and corticosteroids in treating anaphylaxis despite both antihistamines (42) and corticosteroids (43,44) having an onset of action that is delayed and too late to prevent respiratory and/ or cardiovascular arrest, which can occur within minutes (23).…”
Section: Limited Awareness Of the Treatment Of Anaphylaxis By Health mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several cohort studies illustrate the extent of under-treatment of anaphylaxis and the low rate of adrenaline use (12,15,(39)(40)(41), with most cases of anaphylaxis that require hospitalization not receiving an AAI on discharge. Adrenaline is much less commonly used than antihistamines and corticosteroids in treating anaphylaxis despite both antihistamines (42) and corticosteroids (43,44) having an onset of action that is delayed and too late to prevent respiratory and/ or cardiovascular arrest, which can occur within minutes (23).…”
Section: Limited Awareness Of the Treatment Of Anaphylaxis By Health mentioning
confidence: 99%
“…Most patients (62%) received antihistamines, and an increasing number (from 22% to 50%; P < 0.001) received corticosteroids. An US community cohort study (39) identified, in medical records from 1990 to 2000, that among 134 patients with acute anaphylaxis and attending the emergency department, only 36.6% were prescribed AAIs on discharge.…”
Section: Limited Awareness Of the Treatment Of Anaphylaxis By Health mentioning
confidence: 99%
“…Treatment with epinephrine in the emergency department and having an insect sting as the reason for the encounter were significantly associated with receiving a prescription for SIE. Age younger than 18 years was the only factor associated with referral to an allergist [7]. Individuals in our cohort the longest had the opportunity to refill three times (or more if replacement units were needed sooner than the expiration date).…”
Section: Discussionmentioning
confidence: 92%
“…We could not find similar studies in the literature. Campbell et al [7] reviewed medical records from two large community emergency departments representing visits over a 10-year period. Using anaphylaxis-related ICD-9 codes and detailed chart reviews, as well as randomly chosen charts of individuals with related diagnoses, 211 cases were identified that fit the criteria for anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Нередки ошибки диагностики анафилаксии: даже в отделениях интенсивной терапии 57% пациентов с анафилаксией не устанавливается правильный диагноз [1][2][3]. Более того, при адекватной диагностике врачи в 80% случаев не назначают препарат первой линии терапии -эпи-нефрин [4][5][6].В настоящее время Европейская академия аллерго-логии и клинической иммунологии (European Academy of Allergy and Clinical Immunology, EAACI) определяет ана- …”
unclassified